MANAJEMEN RISIKO DALAM PERBANKAN SYARIAH - -, Faisal (MEDIA HUKUM, 2014)
Banking is a Financial Intermediary Institution either as a General Baning or as a Syariah Banking will always face with any kinds of risks with the level complexity variously and stick to its business. The Syariah banking as one of National Banking has gotten the positions by being issued the Acts No. 21 in 2008 about Syariah banking.